(untitled) (Numerus academy review, 2026)
This research paper aims to analyze the determinants of FDI in Algeria for the period 1996-2018 through An Econometric study using ARDL Models, to determine the type of relationship between some economic and institutional variables and FDI flows to Algeria . The study concluded that foreign direct investment to Algeria is affected by these variables on the long run .